Climate change impacts on soil processes and ecosystem properties - Horwath, William R.; Kuzyakov, Yakov (Developments in soil science ;, 2018)
'Climate Change Impacts on Soil Processes and Ecosystem Properties, ' Volume 35 in the Developments in Soil Science series, presents current and emerging soil science research in the areas of soil processes and climate change, while also evaluating future research needs. The book combines the five areas of soil science (microbiology, physics, fertility, pedology and chemistry) to give a comprehensive assessment. This integration of topics is rarely done in a single publication due to the disciplinary nature of the soil science areas. Users will find it to be a comprehensive resource on the topic. Key Features: Provides an analysis of all areas of soil science in the context of climate change impact on soil processes and ecosystem properties; Presents information that is displayed in an accessible form for practitioners and disciplines outside of soil science; Contains a concluding section in each chapter which assesses key areas Includes a discussion on future research directions. Readership: Academic researchers, practitioners, policy developers. --